2020
DOI: 10.1534/genetics.120.303481
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Genetic Architecture Modulates Diet-Induced Hepatic mRNA and miRNA Expression Profiles in Diversity Outbred Mice

Abstract: Genetic approaches in model organisms have consistently demonstrated that molecular traits such as gene expression are under genetic regulation, similar to clinical traits. The resulting expression quantitative trait loci (eQTL) have revolutionized our understanding of genetic regulation and identified numerous candidate genes for clinically-relevant traits. More recently, these analyses have been extended to other molecular traits such as protein abundance, metabolite levels, and miRNA expression. Here we per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Probes and transcript cluster IDs (TC IDs) were first filtered as described [70], resulting in the total number of 24,004 unique probes post-filter corresponding to 23,626 genes. Next, TC IDs were kept for analysis if their median expression was above the mean of all TC ID medians or if their median expression was above the mean of all TC ID medians in over 12.5% of samples, based on the assumption that by chance, one of the 8 founders may be contributing low/no expression alleles.…”
Section: Microarray Analysis For Identification Of Gene Expression Le...mentioning
confidence: 99%
See 1 more Smart Citation
“…Probes and transcript cluster IDs (TC IDs) were first filtered as described [70], resulting in the total number of 24,004 unique probes post-filter corresponding to 23,626 genes. Next, TC IDs were kept for analysis if their median expression was above the mean of all TC ID medians or if their median expression was above the mean of all TC ID medians in over 12.5% of samples, based on the assumption that by chance, one of the 8 founders may be contributing low/no expression alleles.…”
Section: Microarray Analysis For Identification Of Gene Expression Le...mentioning
confidence: 99%
“…Module eigengenes were calculated, and Spearman's correlations were performed between module eigengenes and measured phenotypes. KEGG pathway enrichment and gene ontology analyses were performed on genes within each module using Enrichr as described [70] to see which modules contained genes associated with biological function or diseases. Cytoscape [77] was used to generate a visualization of the relationship between genes within a module, using the magenta module as an example.…”
Section: Weighted Gene Co-expression Network Analysis (Wgcna)mentioning
confidence: 99%
“…The genetic and phenotypic diversity of the combined eight founder strains is similar to the interindividual diversity of the human population. The utilization of the genomic sequence of the eight CC founder strains provides an unprecedented unique resource for genetic mapping and correlation studies (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) Here, we evaluate the variability of metabolic traits and perform global liver transcriptomics from the eight CC founder strains fed a standard purified diet or an atherogenic diet. Our studies focus on female mice as a number of studies have reported that female mice are generally more susceptible to atherosclerosis than male mice (30,32,(35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%